Study of nano-scale Si/SiGe structures for quantum cascade emitters - Lu, Fen (2010)
Silicon is the dominant semiconductor in the microelectronics industry. Over the last 40 years, it has gone through the most amazing technological transformation and growth, which leads to the extraordinary high levels of integrated circuit complexities. The desire to integrate optical and microelectronic functions on the same chip to realize optoelectronic integrated circuits (OEICs) based on silicon ideally requires the active photonic components to be integrated with the silicon-based platform. Silicon-Germanium (SiGe) compound used as optoelectronic emission material attracts more and more attention due to the development of quantum cascade laser (QCL). Many researchers proposed different designs to realize the emission. However, it is yet successful. In this report, we analyzed the mechanisms in QCLs, and calculated the band structure with eight-band k· p method, with strain effect taken into consideration. Based on our calculations, we optimized the design to achieve an emission wavelength in far-infrared region.